UMA TEOPOÉTICA DO ÍNFIMO: A EXPERIÊNCIA DO SAGRADO NA POESIA DE MANOEL DE BARROS - Ludvichak, Dílvia dos Santos (2021)
This master’s thesis studies some poems of the brazilian poet Manoel de Barros and his possible contribution to the advancement of the reflections in the field of Theopoetics. Our starting point will be the path taken by Religion and the immense care that, through Theology, has offered humanity throughout history, and in the recognition of weaknesses, to reach the contingencies and contributions that Literature, and in a very special way, to Poetry can evoke. Our main hypothesis is that Literature, by bordering on existential inconcretions, as well as Theology, has something to say, and that together, they can touch the ground of human life, detached from its finitude. When Christian Theology points to a humanized Jesus, revealed in human experience, and Literature, in its form, expresses and reveals this same experience through words and poetic image, both sciences work already together, blurring the frontiers over and over, in an attitude of completeness. For this discussion, this thesis was based especially on the theoretical texts of authors such as: Karl-Josef Kuschel (1999), Octavio Paz (2014), Gaston Bachelard (2009), Antônio Manzatto (1994) and Rubem Alves (1974, 1979, 1995). In this perspective, we hope that this research will be conducted, leading to perceive signs of transcendental experiments, in the aesthetic project of the poet Manoel de Barros, as he overcomes an inherent human being, as if by an umbilical cord, to nature, - first home - with language, with images, with childhood, in its permanent becoming, a place of the sacred, in an unpretentious invitation to touch the transcendent, not static, unadulterated, not dissociated from life. In this perspective, Literature and Theology can be allied and human existence comes out stronger, because it is better supported.